Selling Fast and Buying Slow: Heuristics and Trading Performance of Institutional Investors - AKEPANIDTAWORN, KLAKOW; MASCIO, RICK DI; IMAS, ALEX; SCHMIDT, LAWRENCE D.W. (Journal of Finance, 2023)
ABSTRACT Are market experts prone to heuristics, and do these heuristics transfer across buying and selling domains? We investigate this question using a unique data set of institutional investors with portfolios averaging $573 million. A striking finding emerges: While there is evidence of skill in buying, selling decisions underperform substantially, even relative to random‐selling strategies. This holds despite the similarity between the two decisions in frequency, substance, and consequences for performance. Evidence suggests an asymmetric allocation of cognitive resources such as attention can explain the discrepancy: We document a systematic, costly heuristic process for selling but not for buying.